Does job satisfaction improve the health of workers? New evidence using panel data and objective measures of health - Justina A. V. Fischer; Alfonso Sousa-Poza (Stockholm School of Economics, The Economic Research Institute (EFI), 2007)
This paper evaluates the relationship between job satisfaction and measures of health of workers using the German Socio-Economic Panel (GSOEP). Methodologically, it addresses two important design problems encountered frequently in the literature: (a) cross-sectional causality problems and (b) absence of objective measures of physical health that complement self-reported measures of health status. Not only does using the panel structure with individual fixed effects mitigate the bias from omitting unobservable personal psycho-social characteristics, but employing more objective health measures such as health-system contacts and disability addresses such measurement problems relating to self-report assessments of health status. We find a positive link between job satisfaction (and changes over time therein) and subjective health measures (and changes therein); that is, employees with higher or improved job satisfaction levels feel healthier and are more satisfied with their health. This observation also holds true for more objective measures of health. Particularly, improvements in job satisfaction over time appear to prevent workers from (further) health deterioration.
Keywords: I18; I19; J28; 330; job satisfaction; well-being; health; panel data analysis; Arbeitszufriedenheit; Gesundheit; Panel; Schweiz